EPEN-30. HISTONE H3 LYSINE 4 TRIMETHYLATION IS A POTENTIAL TARGET TO IMPROVE CHEMOTHERAPEUTIC EFFICACY FOR PEDIATRIC PRIMARY EPENDYMOMAS. Issue 2 (22nd June 2018) - XI, Guifa; Li, Yuping; Hoffman, Lindsey; Hashizume, Rintaro; Lewis, Rebecca; Gravohac, Gordan; Wadhwani, Nitin; Rice, Gavin; Jie, Chunfa; Best, Bemjamin; Saratisis, Amanda; Alden, Tord; et al.
Abstract: Ependymomas are the third most common form of brain tumors in children. These tumors are resistant to chemotherapy and despite genomic sequencing, there is a lack of effective molecular treatment targets. Efficient treatment targets need to be identified. Increasing evidence shows epigenetic alterations including posttranslational histone modifications (PTMs), associated with malignancy, chemotherapeutic resistance and prognosis in pediatric ependymomas. In this study we examined histone PTMs in ependymomas and identified potential targets to improve chemotherapeutic efficacy. Global levels of trimethylation at lysine 4 on histone H3 (H3K4me3), detected with immunohistochemistry and western blots, positively correlated with malignancy in pediatric primary ependymomas. Micro-array analysis of 22 pediatric ependymomoas identified upregulated candidate drug resistance genes. Promoter H3K4me3 occupancy was examined for two of these genes, CCND1 and ERBB2. Chromatin-immunoprecipitation with H3K4me3 coupled with real-time PCR, showed higher levels of H3K4me3 at these genes in grade III tumors, in comparison to grade II ones. When H3K4me3 levels were reduced in primary cultured ependymoma cells in vitro, cell response to chemotherapy increased. In summary, these results indicate that H3K4me3 levels are high at promoters of genes which confer chemotherapeutic resistance. Consequently, a novel treatment regimen which targets H3K4me3 in combination with traditional protocols may increase chemotherapeutic efficacy and improve prognosis for children who present with ependymoma.